Impacts of thermal and cold discharge from power plants on marine benthos and its mitigation measures: a systematic review - Leng, Qingxue; Mohamat-Yusuff, Ferdaus; Mohamed, Khairul Nizam; Zainordin, Nazatul Syadia; Hassan, Mohd Zafri (Frontiers Media SA, 2024)
Introduction: Power plants discharge thermal and cold effluents that significantly alter marine environments, impacting various organisms, including benthic communities. While thermal discharge has received considerable research attention, the impacts of cold discharge remain underexplored. This systematic review synthesizes existing research on the effects of power plant discharges on marine benthic ecosystems. Methods: A systematic literature search was conducted using Scopus, PubMed, and Web of Science, following PRISMA guidelines, covering studies from 1974 to 2024. A total of 58 articles were included in this review. CiteSpace was used to visualize trends, and statistical analysis was conducted to assess relationships between environmental parameters and changes in benthic abundance. Results: A significant negative correlation was observed between temperature differentials, ambient temperature, and benthic abundance. Thermal discharge generally led to reduced benthic diversity and abundance, with occasional increases under low ambient temperatures. Cold discharge effects remain less documented, with evidence primarily focused on phytoplankton and fish. Additionally, dissolved oxygen, pH, and bottom sediment composition were significantly altered by power plant discharge. Detection and mitigation measures are crucial to managing these impacts. Mitigation measures include distributed discharge for cold effluents, advanced heat recovery systems, and careful site selection to minimize impacts on sensitive ecosystems. Long-term management and adaptive strategies are essential to reduce adverse effects and maintain ecological balance. Discussion: Thermal discharges adversely impact marine benthic organisms by decreasing biodiversity and changing community structure, largely due to elevated temperatures and reduced oxygen levels. Cold discharges present unique challenges that require further research to fully understand their ecological impacts. Mitigation measures, such as distributed discharge for cold effluents and advanced heat recovery systems for thermal discharges, are essential to minimize the environmental impact of power plant operations.